The Effects of Virtual Height Exposure on Postural Control and Psychophysiological Stress Are Moderated by Individual Height Intolerance - Bzdúšková, Diana; Marko, Martin; Hirjaková, Zuzana; Kimijanová, Jana; Hlavačka, František; Riečanský, Igor (Frontiers in Human Neuroscience, 2022)
Virtual reality (VR) enables individuals to be exposed to naturalistic environments in laboratory settings, offering new possibilities for research in human neuroscience and treatment of mental disorders. We used VR to study psychological, autonomic and postural reactions to heights in individuals with varying intensity of fear of heights. Study participants (N = 42) were immersed in a VR of an unprotected open-air elevator platform in an urban area, while standing on an unstable ground. Virtual elevation of the platform (up to 40 m above the ground level) elicited robust and reliable psychophysiological activation including increased distress, heart rate and electrodermal activity, which was higher in individuals suffering from fear of heights. In these individuals, compared with individuals with low fear of heights, the VR height exposure resulted in higher velocity of postural movements as well as decreased low-frequency (<0.5 Hz) and increased high-frequency (>1 Hz) body sway oscillations. This indicates that individuals with strong fear of heights react to heights with maladaptive rigidity of posture due to increased weight of visual input for balance control, while the visual information is less reliable at heights. Our findings show that exposure to height in a naturalistic VR environment elicits a complex reaction involving correlated changes of the emotional state, autonomic activity and postural balance, which are exaggerated in individuals with fear of heights.